2020
DOI: 10.3390/cells9092038
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Heparanase Regulates Chromatin Remodeling, Gene Expression and PTEN Tumor Suppressor Function

Abstract: Heparanase (HPSE) is an endoglycosidase that cleaves heparan sulfate and has been shown in various cancers to promote metastasis, angiogenesis, osteolysis, and chemoresistance. Although heparanase is thought to act predominantly extracellularly or within the cytoplasm, it is also present in the nucleus, where it may function in regulating gene transcription. Using myeloma cell lines, we report here that heparanase enhances chromatin accessibility and confirm a previous report that it also upregulates the acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…Based on CHISEL algorithm, they reanalyzed 10× genomics chromium single-cell DNA sequencing data from two patients at early stage of breast cancer (patient 1: a triple negative ductal carcinoma in situ and patient 2: at stage 1 infiltrating ductal carcinoma) and identified large-scale allele-specific copy-number aberrations (CNAs) which, on average, cover ~25% of the genome in at least 100 cells however were uncharacterized by previous used total copy-number analysis. Further investigation into the ~25% CNAs of the genome revealed that the most common type of allele-specific CNAs identified by CHISEL are copy-neutral LOHs and contains several genes which have been reported in the previous 560 breast cancer database [ 114 ], such as ARID1B and ESR1 on chromosome 6q, PTEN on chromosome 10q, BRCA2 and RB1 on chromosome 13, It is worth noting that all the genes undergoing copy-neutral LOHs have been reported in almost all type of tumor cells [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ], indicating that these copy-neutral LOHs mutations may take an important role at an early stage during the tumor evolution.…”
Section: Loss Of Heterozygosity In Tumors Provides Up-and-coming Pmentioning
confidence: 99%
“…Based on CHISEL algorithm, they reanalyzed 10× genomics chromium single-cell DNA sequencing data from two patients at early stage of breast cancer (patient 1: a triple negative ductal carcinoma in situ and patient 2: at stage 1 infiltrating ductal carcinoma) and identified large-scale allele-specific copy-number aberrations (CNAs) which, on average, cover ~25% of the genome in at least 100 cells however were uncharacterized by previous used total copy-number analysis. Further investigation into the ~25% CNAs of the genome revealed that the most common type of allele-specific CNAs identified by CHISEL are copy-neutral LOHs and contains several genes which have been reported in the previous 560 breast cancer database [ 114 ], such as ARID1B and ESR1 on chromosome 6q, PTEN on chromosome 10q, BRCA2 and RB1 on chromosome 13, It is worth noting that all the genes undergoing copy-neutral LOHs have been reported in almost all type of tumor cells [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ], indicating that these copy-neutral LOHs mutations may take an important role at an early stage during the tumor evolution.…”
Section: Loss Of Heterozygosity In Tumors Provides Up-and-coming Pmentioning
confidence: 99%
“…Autophagy induced by lysosomal HPSE has been shown to enhance tumour development and chemoresistance [ 108 , 109 , 110 ]. Although HPSE activity has been mainly described extracellularly or within the cytoplasm, nuclear HPSE has also been reported [ 111 , 112 , 113 ]. In melanoma, nuclear HPSE was shown to suppress tumour progression by competing for DNA binding and inhibiting the transcription of genes, such as those coding for ECM-degrading enzymes that promote metastasis formation [ 112 ].…”
Section: Heparan Sulfate and Heparan Sulfate Proteoglycans Aberranmentioning
confidence: 99%
“…In melanoma, nuclear HPSE was shown to suppress tumour progression by competing for DNA binding and inhibiting the transcription of genes, such as those coding for ECM-degrading enzymes that promote metastasis formation [ 112 ]. In multiple myeloma disease context, HSPE was recently associated with chromatin opening and transcriptional activity concomitant with downregulation of PTEN tumour suppressor activity [ 111 ]. Also supporting the role of HPSE in tumour progression and metastasis formation, HPSE has been shown to promote EV secretion by tumour cells, affecting its protein cargo [ 114 , 115 ], and modulating HS structure on recipient cells to facilitate EVs internalisation [ 9 , 115 , 116 ].…”
Section: Heparan Sulfate and Heparan Sulfate Proteoglycans Aberranmentioning
confidence: 99%
“…Accumulating evidence suggests a role for heparanase in regulating gene transcription also through epigenetic mechanisms [30,79,[91][92][93][94][95][96][97]. Nuclear localization of heparanase, documented in several studies [34,35,96,97] has been associated with increased histone acetylation due to degradation of nuclear HS which acts as inhibitor of HATs [34,35]. To explore the role of the heparanase/ HPSG axis in epigenetic regulation in SS cells, we first examined the effect of heparanase on histone acetylation.…”
Section: Heparanase Is Epigenetically Regulated and Acts As Epigenetic Regulator In Ss Cellsmentioning
confidence: 99%
“…A deregulated heparanase/HSPG system profoundly impacts on tumor aggressiveness by acting both in the tumor microenvironment and inside the tumor cells. Emerging evidence indicates that nuclear heparanase and HSPGs also play a role in regulating histone acetylation and gene expression [33][34][35]. A potential relationship between deregulated heparanase/HSPG axis and oncogenic players in the different sarcoma subtypes remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%